A descriptive model of shared decision making derived from routine implementation in clinical practice ('Implement-SDM'): Qualitative study. Issue 10 (October 2019) - Joseph-Williams, Natalie; Williams, Denitza; Wood, Fiona; Lloyd, Amy; Brain, Katherine; Thomas, Nerys; Prichard, Alison; Goodland, Annwen; McGarrigle, Helen; Sweetland, Helen; Edwards, Adrian
Highlights: We aimed to understand how SDM is actually enacted in routine clinical settings. SDM is more complex than portrayed in previous models. Our descriptive model ('Implement-SDM') reflects SDM by skilled clinicians, adapted for use in routine settings. Abstract: Objective: Research is needed to understand how Shared Decision-Making (SDM) is enacted in routine clinical settings. We aimed to 1) describe the process of SDM between clinicians and patients; 2) examine how well the SDM process compares to a prescriptive model of SDM, and 3) propose a descriptive model based on observed SDM in routine practice. Methods: Patients with chronic kidney disease and early stage breast cancer were recruited consecutively via Cardiff and Vale University Health Board (UK) teams. Consultations were audio-recorded, transcribed and thematically analysed. Results: Seventy-six consultations were observed: 26 pre-dialysis consultations and two consultations each for 25 breast cancer patients. Key stages of the 'Three Talk Model' were observed. However, we also observed more elements and greater complexity: a distinct preparation phase; tailored and evolving integrative option conversation; patients and clinicians developing 'informed preferences'; distributed and multi-stage decisions; and a more open-ended planning discussion. Use of decision aids was limited. Conclusion: A more complex picture was observed compared with previous portrayals in current theoretical models. Practice iImplications: The model can provide a basis for future training and initiatives to promote SDM, and tackle the gap between what is advocated in policy, but rarely achieved in practice.